Travessias pelos corredores da memória: o museu do holocausto na sua constituição discursiva e política - Krümmel, Elivélton Assis (2023)
This research, entitled “Traveling through the corridors of memory: the Holocaust Museum in its discursive and political constitution”, aims to understand how the discursive and political constitution of the Holocaust Museum in Curitiba - PR takes place. Therefore, attentive to the discourse, in its linguistic materiality, associating language with the very construction of the history of society (ORLANDI, 2009), in order to explain a theoretical and analytical point of view that starts from the museum as a place built by from subjects, with a view to the demands that emanate from the social and cultural (VENTURINI, 2017), considering the crossings of the (re)signification of the story(s) of/about the historical event and the (re)construction of the memory(s) of/about the Holocaust. Therefore, depending on the production conditions of my research, carried out in large part during the pandemic, I propose to observe how there is a movement of (de)borderization of this institution, in order to highlight how the incursions/crossings to the institution summon the beat between the digital and physical spaces, which confer a possibility of reinvention of the Museu do Holocausto de Curitiba – PR through socio-historical claims that directed museum transformations. Thus, I explain that the digital (re)signifies certain practices of the subject's relationship with the world, between the subject and history, between the subject and memory, between the subject and language and between the subject and the museum itself. As a result of my crossings, I understand that, in contemporary times, there is a movement of (de)borderization of museums, which is potentialized via the worldwide computer network. Faced with apparent frontiers, the meanings of/about the Holocaust are also constructed in/by the digital discourse, but also by the objects that are exposed by the museum, and it is these relationships that allow, in my gesture of reading and interpretation, the understanding of that, in its incompleteness, the museum institution goes beyond its own limits, promoting drifts to different spaces of meaning, which set in motion new/other meanings between the same and the different. It is in/by (re)inventions and (re)sayings by/about museums, due to the effects of time and space and the beats between history and memory, that a new museological configuration emerges, producing meanings and also constituting the museum in (dis)course in the digital space, promoting an extension of their physical spaces, taking them out of frontiers. So, in/by the structuring effects of the Museu do Holocausto de Curitiba – PR, I explain how the contemporary museum(s), specifically those that are responsible for representing the history and memory of the genocides, select the vestiges of the past and organize discourses to promote and convey a discourse about the past, the present and the future, in their impact on social practices.